2007
DOI: 10.1063/1.2776855
|View full text |Cite
|
Sign up to set email alerts
|

Stability of photovoltage and trap of light-induced charges in ferroelectric WO3-doped (Pb0.97La0.03)(Zr0.52Ti0.48)O3 thin films

Abstract: The stability of photovoltage in WO3-doped (Pb0.97La0.03)(Zr0.52Ti0.48)O3 (PLWZT) ferroelectric thin films was investigated. For in-plane polarized configuration, with a greatly enhanced electrode gap, the reduction ratio of photovoltage during multicycle UV illumination was significantly smaller and stability of photovoltage was greatly improved over the sandwich capacitor configuration. The ferroelectric-metal interfacial effects including Schottky barriers and polarization screening due to the trap of photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 34 publications
(33 reference statements)
3
49
0
Order By: Relevance
“…41,42 It is clear that FPV effects may become very small when the average internal electric field in FNC is zero. [16][17][18][19][20][21][22][23][24] In this case, the photocurrent is only due to charge transport via diffusion.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 4 more Smart Citations
“…41,42 It is clear that FPV effects may become very small when the average internal electric field in FNC is zero. [16][17][18][19][20][21][22][23][24] In this case, the photocurrent is only due to charge transport via diffusion.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…[1][2][3][24][25][26] Both experimental and theoretical works have shown that the FPV effect is different from that in conventional p-n junctions or Schottky barriers of the semiconductors. [18][19][20][21][22][23][24][25][26][27] Although a complete understanding of the physical mechanisms involved in the FPV effect in metal-ferroelectric-metal ͑MFM͒ structures with the shortcircuit boundary conditions has not yet been accomplished, a widely accepted explanation of the photoelectric current is the separation of the photon-generated electron-hole pairs ͑excitons͒ by the internal electric field, [20][21][22][23][24] which also provides the potential difference that drives the photocurrent in the external circuit connected to the ferroelectrics. In absence of an external electric field, the internal electric field comes from the depolarization field produced by polarization screening charges in the metal electrodes and the inhomogeneous polarization distribution near interfaces.…”
Section: ͑Pzt͒mentioning
confidence: 99%
See 3 more Smart Citations